Effect of Ag additions on the reverse martensitic transformation in the Cu-10 mass% Al alloy - Adorno, A. T.; Silva, RAG (Springer, 2006)
The effect of Ag additions on the reverse martensitic transformation in the Cu-10 mass% Al alloy was studied using differential thermal analysis (DTA), optical (OM) and scanning electron microscopies (SEM) and X-ray diffractometry. The results indicated that Ag additions to the Cu-10 mass% Al alloy shift the equilibrium concentration to higher Al contents, allow to obtain both beta(1)' and beta' martensitic phases in equilibrium and that Ag precipitation is a process associated with the perlitic phase formation.
Keywords: Ag additions; Cu-based alloys; reverse martensitic transformation